Tinjauan Yuridis Terhadap Tindak Pidana Pemalsuan Uang Kertas Rupiah di Indonesia - Dinda Dian Pratiwi; I Nyoman Gede Sugiartha; Luh Putu Suryani (Jurnal Preferensi Hukum, 2021)
Humans need money to be able to meet their needs. Money has a very important role, this causes some people to try to have money in a way that is against the law. With the help of science and technology, it can make it easier for humans to do counterfeiting rupiah banknotes. The purpose of this research is to reveal the regulation of the criminal act of counterfeiting rupiah banknotes in Indonesia and criminal sanctions against the criminal act of counterfeiting rupiah banknotes in Indonesia. The type of research is normative legal research with a conceptual approach that is outlined descriptively with legal arguments. The collection of legal materials is done by means of a literature research. Sources of data used are primary, secondary and tertiary sources of legal material and analyzed systematically. The results of the research reveal that the regulation of criminal acts of counterfeiting rupiah banknotes in Indonesia is regulated in Article 11 of Law Number 7 of 2011 concerning Currency concerning Bank Indonesia is an institution authorized to manage rupiah currency and Article 26 paragraph (1) of Law Number 7 The year 2011 concerning Currency regulates the prohibition against counterfeiting rupiah currency. In addition, it is regulated in Article 244 of the Criminal Code which prohibits criminal acts of counterfeiting money, if violated, sanctions will be imposed according to applicable regulations. Criminal sanctions for counterfeiting rupiah banknotes in Indonesia are contained in Article 36 paragraph (1) of Law Number 7 of 2011 concerning Currency and Article 244 of the Criminal Code